Biochemical changes in liver and muscle of the cichlid, Oreochromis mossambicus (Peters, 1852) exposed to sub-lethal concentration of mercuric chloride - George K, Roy; Nair, A, Malini (Indian Journal of Fisheries, 2012)
Heavy metals, as environmental stressors, may alter tissue biochemical parameters in fishes. Oreochromis mossmabicus, was exposed to different sub-lethal concentrations of mercuric chloride @ 0.5, 1.0 and 2 ppm to investigate changes in tissue biochemical parameters on 0, 7th and 14th day of exposure. Protein content in the liver and muscle was found depleted due to proteolysis induced by mercury toxicity. The level of liver and muscle glycogen also declined, indicating increased utilisation of glucose to counteract the increased energy demand imposed by severe anaerobic stress of mercury toxicity. The alterations in the alkaline and acid phosphatase activities during exposure period were associated with tissue damage and impaired enzyme activities resulting from toxicity of mercury.